A students' guide to Piaget - Boyle, D. G. (Commonwealth and international library of science, technology, engineering and liberal studies. Psychology division., 1969)
A Students' Guide to Piaget is a students' guide to the work of Jean Piaget, one of the most influential thinkers in contemporary psychology. It discusses Piaget's multifarious epistemological interests, his developmental psychology, and his solutions to the problems of mathematical epistemology. Piaget's contributions to education, as well as his early work on children's language and cognitive development, are also examined. This book is comprised of 10 chapters and begins with an overview of the major problem that confronts students when they first encounter Piaget's work: why he has done it.